Evaluación de normativas ACI 365.1R y EHE-08 para la predicción de vida útil por ataque de cloruros en edificios afectados por corrosión - Mucching Toscano, Jorge Antonio (2024)
In order to assess the applicability of the service life prediction models ACI 365.1R and EHE-08, an experimental campaign was conducted on six structures affected by corrosion in the vicinity of the Peruvian coastline. The study involved visual inspections, steel auscultation, carbonation tests, extraction of diamond core samples, and sampling of crushed concrete. Subsequently, the samples underwent compressive strength tests and chloride concentration determination on concrete surfaces. The collected information was analyzed using dispersion measures and statistical methods. The results revealed that the European model EHE-08 provides a less conservative estimate of service life, with an average of 44 years and the widest range of periods, spanning 66 years. This model also exhibited the greatest dispersion among the cases studied, coupled with the lowest coefficient of variation at 22%. On the other hand, the American model ACI 365 presented a more conservative service life estimate, with an average of 16 years and a narrower range of values, limited to 10 years. This model showed the least dispersion and one of the lowest coefficients of variation at 23%. Pearson correlation analyses and ANOVA demonstrated a notable similarity between both models, as reflected in the proximity of the results. However, the European model EHE-08 is more straightforward in execution and presentation. Therefore, it is the primary choice for this study.